2019
DOI: 10.1111/jfpe.13351
|View full text |Cite
|
Sign up to set email alerts
|

Effective removal of organophosphorus pesticide residues in tomatoes using natural extracts

Abstract: The reduction efficiency of the extracts of Albizia amara and Acacia concinna against most widely used organophosphorus pesticides such as dimethoate, malathion, dichlorvos, and chlorpyrifos on tomato samples was investigated. The pesticide residues were quantified by gas chromatography with triple quadrupole mass spectrometer (GC-MS/MS). The maximum reduction efficiency was achieved from the samples treated with 8% A. concinna extract on dichlorvos (87%) and dimethoate (84%) followed by 6% A. amara on malathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, it was reported that ozone treatment produced toxic by-product from the parent pesticides and also reduced the nutritional quality of treated green bell pepper (Swami et al, 2021). The pesticide mitigation efficiency of TILE and AILE in green bell pepper was found to be high when compared to previously studied strawberry sample (Venkatachalapathy et al, 2020). At the same time, Renuka et al (2022) reported that the extracts of Acacia concinna and Albizia amara showed higher pesticide mitigation in tomato.…”
Section: Effect Of Plant Extracts On the Mitigation Of Pesticidesmentioning
confidence: 88%
See 3 more Smart Citations
“…However, it was reported that ozone treatment produced toxic by-product from the parent pesticides and also reduced the nutritional quality of treated green bell pepper (Swami et al, 2021). The pesticide mitigation efficiency of TILE and AILE in green bell pepper was found to be high when compared to previously studied strawberry sample (Venkatachalapathy et al, 2020). At the same time, Renuka et al (2022) reported that the extracts of Acacia concinna and Albizia amara showed higher pesticide mitigation in tomato.…”
Section: Effect Of Plant Extracts On the Mitigation Of Pesticidesmentioning
confidence: 88%
“…The operating conditions such as pre-test speed, test speed and post speed were 1.5 mm/s, 1 mm/s, and 10 mm/s, respectively. The probe with a 5 mm distance, automatic force detection, a 50 kg load cell, a 5 g of trigger force and data acquisition rate at 400 points per second (PPS) (Venkatachalapathy et al, 2020).…”
Section: Texture Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The suppression effect occurred due to the washing activity of the profenofos residue on the leaf mustard. One of the compounds playing an important role in washing pesticide residues is saponins (44). The three plant aqueous extract tested were reported to contain saponins.…”
Section: The Effect Of Plant Aqueous Extract On Profenofos Residuementioning
confidence: 99%